Auditoría integral de logística y rendimiento financiero de la empresa SERVIPAXA S.A, año 2017 - Medina Armas, Angélica Tamara (2018)
This research work was conducted in the company Servipaxa SA, created in the city of Quevedo according to registration 115482, located at Km 1 Via Valencia, in the San Cristobal parish belonging to the canton Quevedo, whose main economic activity is the sale to wholesale and retail of agrochemical products, fertilizers and banana plastic bags, the same that is responsible for distributing to the haciendas belonging to the Manobanda SA Group, and to the different companies at local and national level, interested in acquiring their products. The objective of the research is to evaluate the impact of the integral audit of logistics on the economic-financial performance of the company Servipaxa SA, seeking to make an assessment of the different elements that are part of the logistics area such as entries, locations, replacements, preparation of orders and shipments of agrochemicals, fertilizers, and banana plastic bags, the same that can not be made is likely to affect the activities inherent to the company's operating departments such as Accounting, Sales, Collections, Production and Marketing, which can finally disrupt the normal development of the daily activities of the organization. As a population and study sample, the operations carried out were analyzed through the elaboration of internal control questionnaires in the area of Accounting, Sales, Collection, Production and Marketing. The analysis of results included the application of working papers, findings sheets, matrices of assessment of inherent risk, risk of control, risk of detection of operational audit among other resources used for the generation of conclusions and recommendations in the development of this research, which aims to directly benefit the managers and officers of the company providing them with information that affects correct decision making and indirectly to customers who provide the goods and services provided by this company. Key words: Integral audit, logistics, financial performance, internal control